Hydrolytic Degradation of Actuators Based on Copolymer Networks From Oligo(ε-caprolactone) Dimethacrylate and n-Butyl Acrylate. (8th April 2019) - Balk, M.; Behl, M.; Lendlein, A.
ABSTRACT: Shape-memory polymer actuators often contain crystallizable polyester segments. Here, the influence of accelerated hydrolytic degradation on the actuation performance in copolymer networks based on oligo(ε-caprolactone) dimethacrylate (OCL) and n-butyl acrylate is studied. The semi-crystalline OCL was utilized as crosslinker with molecular weights of 2.3 and 15.2 kg∙mol −1 (ratio: 1:1 wt%) and n-butyl acrylate (25 wt% relative to OCL content) acted as softening agent creating the polymer main chain segments within the network architecture. The copolymer networks were programmed by 50% elongation and were degraded by means of alkaline hydrolysis utilizing sodium hydroxide solution (pH = 13). Experiments were performed in the range of the broad melting range of the actuators at 40 °C. The degradation of test specimen was monitored by the sample mass, which was reduced by 25 wt% within 105 d. As degradation products, fragments of OCL with molecular masses ranging from 400 to 50.000 g·mol -1 could be detected by NMR spectroscopy and GPC measurements. The cleavage of ester groups included in OCL segments resulted in a decrease of the melting temperature (Tm ) related to the actuator domains (amorphous at the temperature of degradation) and simultaneously, the Tm associated to the skeleton domain was increased (semi-crystalline at the temperature of degradation). The alkaline hydrolysis decreased the polymer chain orientation of OCL domains until a random alignment of crystalline domains was obtained. This result was confirmed by cyclic thermomechanical actuation tests. The performance of directed movements decreased almost linearly as function of degradation time resulting in the loss of functionality when the orientation of polymer chains disappeared. Here, actuators were able to provide reversible movements until 91 d when the accelerated bulk degradation procedure using alkaline hydrolysis (pH = 13) was applied. Accordingly, a lifetime of more than one year can be guaranteed under physiological conditions (pH = 7.4) when, e.g., artificial muscles for biomimetic robots as potential application for these kind of shape-memory polymer actuators will be addressed.